The Robbery of Financial Institutions in Witbank Policing Area, South Africa - Samuel Khehla Nkosi; Jacob Tseko Mofokeng (Journal of Islamic Economics and Business, 2023)
The motives for violent crime are wide ranging. Results show that violence in commercial robbery was often used to achieve the material goals of the offense (to steal money or goods) by ensuring compliance and by overcoming resistance. Also found was that violence in assault was used purposively to achieve the immediate goal of harming the victim. In both cases, violence was used in ways that could be directly attributed to the successful commission of the offense. In other cases, violence performed additional functions, such as enhancing the status of the offender, generating a reputation for toughness on the street, providing a response to challenges to masculinity, giving an outlet for aggression and the desire to fight, and as a means of administering retaliation and revenge through informal justice; violence of this kind is used as an expression of a value system that condones violent behavior. Methodologically, the research is qualitative, involving semi-structured face-to-face oral interviews (open-ended) with 30 armed robbers in prison custody in Witbank, South Africa. Armed robbery is a type of robbery aided by weapon(s) to threaten, force and deprive a person or persons of the right to private, public or corporate belongings. The analytical framework employed is interpretive phenomenology, to capture the holistic worldview of the offender sample. Secondary data comes from both the eletronic media. Findings are presented under four systematic themes: “challenges of policing bank robberies and the extent of the harm, speculative motives, planning and duration of planning process, and tools of trade”. In the following, these themes are explained making use of participants’ statements.